Bisphenol A exposure induces metabolic disorders and enhances atherosclerosis in hyperlipidemic rabbits. Issue 9 (23rd January 2015) - Fang, Chao; Ning, Bo; Waqar, Ahmed Bilal; Niimi, Manabu; Li, Shen; Satoh, Kaneo; Shiomi, Masashi; Ye, Ting; Dong, Sijun; Fan, Jianglin
ABSTRACT: Bisphenol A (BPA) is an artificial environmental endocrine disrupter. Excess exposure to BPA may induce many disorders in the metabolism and cardiovascular system. However, the underlying toxicological mechanisms remain largely unknown. In this study, we administered genetically hyperlipidemic Watanabe heritable hyperlipidemic (WHHL‐MI) rabbits (male, 14 week old), which have more common features with humans than the mouse and rat especially in the metabolism and cardiovascular system, with BPA at 40 mg kg –1  day –1 for 8 weeks by gavage and compared their plasma lipids, glucose and insulin response with those of the vehicle group. All of the rabbits were sacrificed, and their pancreas, liver, adipose tissue, heart and aorta were analyzed using histological and morphometric methods. Furthermore, we treated human hepatoma HepG2 cells and human umbilical cord vein endothelial cells (HUVECs), with different doses of BPA based on the serum BPA levels in the WHHL rabbits for 6 h to investigate the possible molecular mechanisms. Our results showed that BPA‐treated rabbits showed insulin resistance, prominent adipose accumulation and hepatic steatosis. Additionally, BPA exposure also caused myocardial injury and enhanced the development of atherosclerosis in the aortic arch with increased macrophage number (86%) and advanced lesion areas (69%). Increased expression of inflammatory genes found in the liver of BPA‐treated rabbits along with the up‐regulation of ER stress, lipid and glucose homeostasis and inflammatory genes in the cultured HepG2 cells and HUVECs suggest that BPA may induce metabolic disorders and enhance atherosclerosis through regulating above molecular pathways in the liver and endothelium. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Watanabe heritable hyperlipidemic (WHHL‐MI) rabbits were used to investigate the detrimental effects of bisphenol A (BPA), which has much more common features with humans than mouse and rat especially in the metabolism and cardiovascular system. BPA exposure resulted in insulin resistance, prominent adipose accumulation, hepatic steatosis and myocardial injury. Moreover, BPA exposure also accelerated the development of atherosclerosis in the aortic arch. BPA may exert its toxic effects through eliciting endoplasmic reticulum (ER) stress and an inflammatory reaction.